Optimizing screening for depression, anxiety disorders, and post-traumatic stress disorder in inpatient addiction treatment: A preliminary investigation. (January 2021) - Levitt, E.E.; Syan, S.K.; Sousa, S.; Costello, M.J.; Rush, B.; Samokhvalov, A.V.; McCabe, R.E.; Kelly, J.; MacKillop, J.
Highlights: Widely-used psychiatric screens functioned adequately in inpatient addiction treatment. Accuracy improved by increasing the cutoff score for the Patient Health Questionnaire-9. Accuracy improved by increasing cutoff score for Post-Traumatic Stress Disorder Checklist for DSM-5. Abstract: Objective: Substance use disorders (SUD) are frequently comorbid with other psychiatric conditions, but a comprehensive diagnostic assessment is often not feasible clinically. Efficient psychometrically-validated screening tools exist for commonly comorbid conditions, but cutoff accuracies have typically not been evaluated in addiction treatment settings. This study examined the performance of several widely-used screening measures in relation to diagnostic status from a clinical interview to identify and validate cutoff scores in an inpatient SUD treatment setting. Method: Participants were 99 patients in a large residential SUD treatment program in Ontario, Canada. Participants completed a screening battery, including the Patient Health Questionnaire – 9 (PHQ-9), Generalized Anxiety Disorder – 7 (GAD-7), and Post-Traumatic Stress Disorder Checklist-5 (PCL-5), and underwent a semi-structured diagnostic clinical interview. Receiver operating characteristic curves were used to determine optimal cutoff scores on the screening tool against the interview-based diagnosis. Results: Area under the curve (AUC) was statistically significant for all screens and were as follows: PHQ-9 = 0.70 (95% CI = 0.59–0.80), GAD-7 = 0.74 (95% CI = 0.63–0.84), and PCL-5 = 0.79 (95% CI = 0.66–0.91). The optimal accuracy cutoff scores based on sensitivity and specificity were: PHQ-9 ≥ 16, GAD-7 ≥ 9, the PCL-5 ≥ 42. Conclusions: In general, the candidate screeners performed acceptably in this population. However, the optimal cutoff scores were notably higher than existing guidelines for depression and PTSD, potentially due to the general elevations in negative affectivity among individuals initiating SUD treatment. Further validation of these cutoff values is warranted. Public health significance: This study provides modified screening cutoff scores for major depression, anxiety disorders, and post-traumatic stress disorder in addiction treatment settings.